1999
DOI: 10.1111/j.1600-0668.1999.t01-3-00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Chamber Testing of Adsorption of Volatile Organic Compounds (VOCs) on Material Surfaces

Abstract: A simple test chamber method to quantify adsorption and desorption of organic compounds on material surfaces is described. Important environmental parameters such as temperature, relative humidity and air velocity were varied and controlled independently around typical indoor values. Experiments were performed with alpha-pinene and toluene in concentrations of 160-300 micrograms/m3. The measurements show adsorption on and desorption from wool carpet, nylon carpet, polyvinyl chloride (PVC) floor coverings, cott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…32 On the other hand, the slow rate of depletion was surprising, given the very high flow velocity in the exhaust manifold. However, the results are in qualitative accord with the findings of Jorgensen, who concluded that flow rate was not an important influence on sorption processes of organics in test chamber experiments, 2 and with the fact that sorption would be the rate limiting process in depletion. Certainly the depletion function would be expected to be more complex than a single exponential because of the varied nature of the surfaces in the hood ventilation system.…”
Section: Temporal Changes In the Surface Chemistry Of The Particulatessupporting
confidence: 91%
See 1 more Smart Citation
“…32 On the other hand, the slow rate of depletion was surprising, given the very high flow velocity in the exhaust manifold. However, the results are in qualitative accord with the findings of Jorgensen, who concluded that flow rate was not an important influence on sorption processes of organics in test chamber experiments, 2 and with the fact that sorption would be the rate limiting process in depletion. Certainly the depletion function would be expected to be more complex than a single exponential because of the varied nature of the surfaces in the hood ventilation system.…”
Section: Temporal Changes In the Surface Chemistry Of The Particulatessupporting
confidence: 91%
“…At higher masses, cluster ions containing CHA were also observed, which provided additional insight into the chemical nature of the surface. The most abundant of the cluster ions corresponded to [((CHA)H) 2 …”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…Among the VOCs detected, toluene and α -pinene from a sofa sample recorded the largest mean equilibrium concentrations (353 and 189  μ g/m 3 , resp.). Reference [33] used the toluene and α -pinene to evaluate VOC emission rates from a number of potential sources, including wool carpet, nylon carpet, and cotton curtain. These authors conducted two types of experiments to induce both adsorption (in which toluene and α -pinene were introduced into the chamber) and desorption (in which only clean air was brought in).…”
Section: Resultsmentioning
confidence: 99%
“…However, in actual apartment bedrooms, VOCs emitted from MRs can be adsorbed onto the surface of furniture such as beds and closets. In addition, building International Journal of Environmental Analytical Chemistry 1135 finishing materials such as walls, floors and ceilings can also adsorb VOCs [24][25][26]. Indoor chemistry would be insignificant as regards the discrepancy of measured and estimated data for BTEX, since these compounds are inert [27].…”
Section: Voc Levels In Apartment Bedroommentioning
confidence: 97%